2009
DOI: 10.1016/j.freeradbiomed.2008.09.032
|View full text |Cite
|
Sign up to set email alerts
|

The overlapping roles of manganese and Cu/Zn SOD in oxidative stress protection

Abstract: In various organisms, high intracellular manganese provides protection against oxidative damage through unknown pathways. Herein we use a genetic approach in S. cerevisiae to analyze factors that promote manganese as an anti-oxidant in cells lacking Cu/Zn superoxide dismutase (sod1Δ). Unlike certain bacterial systems [1], oxygen resistance in yeast correlates with high intracellular manganese without a lowering of iron. This manganese for anti-oxidant protection is provided by the Nramp transporters Smf1p and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 59 publications
2
131
0
1
Order By: Relevance
“…To alter phosphate levels specifically, we targeted the Vph1p subunit of the vacuolar ATPase, needed for phosphate accumulation (4,25), and the Pho85p kinase, which negatively controls phosphate uptake and storage (25)(26)(27). As shown in Table 1, the resulting vph1 and pho85 strains respectively exhibit a fourfold decrease and an eightfold increase in cellular Pi, polyphosphate (pP), and total phosphates concentrations, with negligible changes in manganese concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To alter phosphate levels specifically, we targeted the Vph1p subunit of the vacuolar ATPase, needed for phosphate accumulation (4,25), and the Pho85p kinase, which negatively controls phosphate uptake and storage (25)(26)(27). As shown in Table 1, the resulting vph1 and pho85 strains respectively exhibit a fourfold decrease and an eightfold increase in cellular Pi, polyphosphate (pP), and total phosphates concentrations, with negligible changes in manganese concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the sod1 pmr1 mutant has the greatest [Mn-Pi] concentration and is most resistant to oxygen stress, whereas the sod1 smf2 and sod1 pho85 mutants have the smallest [Mn-Pi] and are most sensitive to oxygen. It is important to note that without the application of ENDOR spectroscopy, one might have reached the opposite conclusion based on the analytical results, namely, that in vivo manganesePi interactions do not correlate with oxidative stress resistance (4). The present use of ENDOR to probe whole-cell Mn 2þ speciation, which allows us to distinguish between Mn 2þ -Pi and Mn 2þ -pP, thus reveals the potential hazard of assuming a transition metal speciation based on altered total cellular concentrations of a given ligand, thereby highlighting the importance of in situ biophysical techniques to probe metal speciation.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that 1 mM Mn 2þ offers some radioprotection to ataxia telangiectasia cells, but is significantly less efficient than 1 mM of a more potent SOD mimic, Mn porphyrin MnTnHex-2-PyP 5þ (255 (193). The role of Mn transporters also was addressed, and carboxylates rather than phosphates were suggested as possible ligand carriers for Mn 2þ (267). Data by Reddi et al (267) are in agreement with our study, in which Mn oxo=hydroxo=acetato complexes, present as a non-innocent impurity in ill-purified MnTBAP 3À preparations, are responsible for the SOD-like activity (264 , and particularly when mechanistic purposes are the goal of the study, it is important to have Mn-based antioxidants very pure and devoid of ''free'', residual Mn 2þ in any form.…”
Section: B the Effects Of Manganese In Vitro And In Vivomentioning
confidence: 89%
“…31 In most tissues, the first line of defense against oxidative stress is the endogenous antioxidant defense system such as SODs: SOD1 in the cytoplasm, SOD2 in mitochondria, and SOD3 in the extracellular space. 32 Furthermore, free radical insult might activate PARP and culminate in an apoptotic cascade. 33 Caspase-3 is a potent, terminal caspase that executes apoptosis.…”
Section: Discussionmentioning
confidence: 99%